Renal function and the long‐term clinical outcomes of cardiac resynchronization therapy with or without defibrillation. Issue 6 (3rd April 2019) - Leyva, Francisco; Zegard, Abbasin; Taylor, Robin; Foley, Paul W.X.; Umar, Fraz; Patel, Kiran; Panting, Jonathan; Ferro, Charles J.; Chalil, Shajil; Marshall, Howard; Qiu, Tian
Abstract: Background and Aims: Patients with moderate‐to‐severe chronic kidney disease (CKD) are underrepresented in clinical trials of cardiac resynchronization therapy (CRT)‐defibrillation (CRT‐D) or CRT‐pacing (CRT‐P). We sought to determine whether outcomes after CRT‐D are better than after CRT‐P over a wide spectrum of CKD. Methods and Results: Clinical events were quantified in relation to preimplant estimated glomerular filtration rate (eGFR) after CRT‐D (n = 410 [39.2%]) or CRT‐P (n = 636 [60.8%]) implantation. Over a follow‐up period of 3.7 years (median, interquartile range: 2.1–5.7), the eGFR < 60 group (n = 598) had a higher risk of total mortality (adjusted hazard ratio [aHR]: 1.28; P = 0.017), total mortality or heart failure (HF) hospitalization (aHR: 1.32; P = 0.004), total mortality or hospitalization for major adverse cardiac events (MACEs, aHR: 1.34; P = 0.002), and cardiac mortality (aHR: 1.33; P = 0.036), compared to the eGFR ≥ 60 group (n = 448), after covariate adjustment. In analyses of CRT‐D versus CRT‐P, CRT‐D was associated with a lower risk of total mortality (eGFR ≥ 60 HR: 0.65; P = 0.028; eGFR < 60 HR: 0.64, P = 0.002), total mortality or HF hospitalization (eGFR ≥ 60 aHR: 0.66; P = 0.021; eGFR < 60 aHR: 0.69, P = 0.007), total mortality or hospitalization for MACEs (eGFR ≥ 60 aHR: 0.70; P = 0.039; eGFR < 60 aHR: 0.69, P = 0.005), and cardiac mortality (eGFR ≥ 60 aHR: 0.60; P = 0.026; eGFR < 60 aHR: 0.55; P = 0.003). Conclusion: In CRT recipients, moderate CKD is associated with a higher mortality and morbidity compared to normal renal function or mild CKD. Despite less favorable absolute outcomes, patients with moderate CKD had better outcomes after CRT‐D than after CRT‐P.